Fiscal or bailout union: Where is the EU - Marek Dabrowski (Center for Social and Economic Research (CASE), 2013)
The European debt crisis triggered a debate on the lacking components of the EU and EMU integration architecture. Many believe that a common currency requires closer fiscal and political integration as a condition for its survival. This opinion is not necessarily supported by the experience of other monetary unions, especially those created by sovereign states. On the other hand, the current EU integration architecture already contains several elements of fiscal union. Furthermore, in several important policy areas such as financial supervision, defense, security, border protection, foreign policy, environmental protection, and climate change, the centralization of tasks and resources at the Union level could offer increasing returns to scale and a better chance to address pan-European externalities. This applies to the entire EU, not only to the Eurozone. Each variant of fiscal integration must be based on sound foundations of fiscal discipline. Market discipline, i.e., the danger of sovereign default, supplemented by clear and consistently enforced fiscal rules is the best solution to this problem. Unfortunately, since 2010, the 'no bail out' principle has been replaced by a policy of conditional bailout of governments in fiscal trouble. Some proposals, such as Eurobonds or the lender of last resort to governments, go even further in this direction, and threaten to build a dysfunctional fiscal union.
Keywords: F33; F55; H77; H87; 330; Monetary Union; Common Currency; Fiscal Union; European Union; Eurozone; EU Budget; Fiscal Federalis; Fiscal Discipline